Repetitive transcranial magnetic stimulation reduces cigarette consumption in schizophrenia patients - Prikryl, Radovan; Ustohal, Libor; Kucerova, Hana Prikrylova; Kasparek, Tomas; Jarkovsky, Jiri; Hublova, Veronika; Vrzalova, Michaela; Ceskova, Eva (Progress in neuro-psychopharmacology & biological psychiatry, 2014)
INTRODUCTION: High-frequency repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex (DLPFC) seemed to decrease tobacco consumption and craving in nicotine-dependent people without psychiatric disorder or otherwise healthy people. Even if the prevalence of cigarette smoking in schizophrenia patients is high and estimated to be between 45% and 88%, this technique has not been systematically studied in this indication in schizophrenia yet. THE AIM OF THE STUDY: The aim of this study was to test the ability of high-frequency (10Hz) rTMS over the left DLPFC to decrease cigarette consumption in schizophrenia patients. METHODS: The study included 35 male schizophrenia patients on stable antipsychotic medication. The patients were divided into two groups: the first (18 patients) were actively stimulated and the second (17 patients) underwent sham (placebo) stimulation. The sham rTMS was administered using a purpose-built sham coil that was identical in appearance to the real coil and made the same noise but did not deliver a substantial stimulus. The rTMS was administered at the stimulation parameters: location (left dorsolateral prefrontal cortex: DLPFC), intensity of magnetic stimulation in % of motor threshold (110%), stimulation frequency (10Hz), number of trains (20), single train duration (10s), inter-train interval (30s), and total number of stimulation sessions (21). In each stimulation session, 2000TMSpulses were given, with a total of 42,000pulses per treatment course. Patients noted the number of cigarettes smoked in the 7days before treatment, during the whole stimulation treatment (21days), and again for a 7-day period after treatment. RESULTS: Cigarette consumption was statistically significantly lower in the actively stimulated patients than in the sham rTMS group as early as the first week of stimulation. No statistically relevant correlations were found in the changes of ongoing negative or depressive schizophrenia symptoms and the number of cigarettes smoked. CONCLUSION: High-frequency rTMS over the left DLPFC has the ability to decrease the number of cigarettes smoked in schizophrenia patients.
Keywords: EEG; Prefrontal Cortex; Positive and Negative Syndrome Scale; Humans; prefrontální mozková kůra; MT; rTMS; lidé středního věku; Calgary Depression Scale for schizophrenia; Double-Blind Method; mladý dospělý; dospělí; motor threshold; prevence kouření; Stimulation; lidé; dvojitá slepá metoda; transkraniální magnetická stimulace; ICD-10; schizofrenie (psychologie); Schizophrenia; dorsolateral prefrontal cortex; EMG; Schizophrenic Psychology; repetitive transcranial magnetic stimulation; odvykání kouření; určení symptomu; Adult; Smoking Cessation; CDSS; Male; Dorsolateral prefrontal cortex; Middle Aged; MINI; electromyography; PANSS; Adolescent; analysis of variance; DLPFC; Transcranial Magnetic Stimulation; International Classification of Diseases, revision 10; electroencephalography; MADRS; Montgomery and Asberg Depression Scale; Young Adult; Consumption; Smoking; mužské pohlaví; kouření; ANOVA; Smoking Prevention; Mini-International Neuropsychiatric Interview; mladiství; Symptom Assessment